Combination of SPH and SP80 prolongs the lifespan of Bacillus subtilis natto to enhance industrial menaquinone-7 biosynthesis - Liu-xiu Hu; Liu-xiu Hu; Yu Chen; Yu Chen; Hong-ping Zhou; Wei Tao; Xu-li Gao; Chuan-chao Wu; Chuan-chao Wu; Hui-min Zhang; Hui-min Zhang; Ru-meng Han; et al. (Frontiers in Microbiology)
Menaquinone-7 (MK-7) production from renewable feedstocks using Bacillus subtilis natto provides a promising pathway toward sustainability. However, MK-7 yields are often limited by poor microbial cell viability. In this study, a novel fermentation strategy aimed at prolonging the lifespan of B. subtilis natto was investigated to enhance MK-7 biosynthesis. The results showed that the combination of soy protein hydrolysate (SPH) and Span 80 (SP80) increased intracellular and extracellular MK-7 yields by 5.6- and 7.2-fold, respectively, compared to the SP-based medium. This enhancement was associated with an extended lifespan of B. subtilis natto, as evidenced by increased optical density and cell length, and a reduced cell death rate—13.5% in the stationary phase compared to 39.5% in the SP-based medium. Moreover, a significant correlation was observed between key MK-7 biosynthetic genes and lifespan-related genes. The expression of growth-related autolysis genes skfF and sdp, which contribute to reduced cannibalism, was downregulated by 4.89- and 5.19-fold, respectively. In contrast, expression of the cell division genes ftsZ and ftsL, which promote cell division, was upregulated by 7.52- and 6.31-fold, respectively. Improved fermentation performance was attributed to a 2.26-fold increase in oligopeptides (Mw < 1 kDa) and moderate levels of amino acids, particularly Phe, Arg, and Glu, derived from the enzymatic hydrolysis of soy protein by Protamex 1.6, present in the SPH+SP80 medium. Meanwhile, the prolonged lifespan also promoted MK-7 biosynthesis by upregulating key membrane-associated genes such as menA and menD, which showed 1.43- and 1.47-fold increases in expression, respectively. This contributed to improved MK-7 precursor availability and enhanced MK-7 assembly efficiency in B. subtilis natto. Collectively, these results indicate that prolonging the lifespan of B. subtilis natto using SPH+SP80 represents a promising and effective strategy for improving industrial MK-7 production.